Dead Man’s Gun: True Crime in Post War Ottawa, 1945-1946 - Burtch, Andrew (Ontario History)

(untitled) (The Ontario Historical Society, 2010)
Just after the war, the city of Ottawa expanded its borders as the federal government created what would become the National Capital Region. The Canadian War Museum was one of the newly created federal institutions. Using recently released documents from the Department of Justice, this article explores how a gun stolen from the museum in October 1945 was later used in the fatal shooting of an Ottawa policeman. The theft, murder, and trial that followed reveal how the Second World War shaped Ottawa and its residents. The crime and its punishment linked in to postwar social and political debates about housing, criminality, and the regulation of souvenir firearms held by Canadian veterans.